Timing of peak pelvis and thorax rotation velocity in baseball pitching - Erik van der Graaff; Marco (MJM); Martijn Nijhoff; Michael Davidson; Merel Hoezen; Dirkjan (HEJ) (Japanese Society of Physical Fitness and Sports Medicine, 2018)
The objective of the present study was to examine the magnitude and timing of peak pelvis and thorax rotations in achieving high throwing velocities in pitching fastballs. During the preseason (Test 1 or T1) and four months later (Test 2 or T2), kinematic analysis was performed on eight elite youth pitchers throwing fastballs. Peak rotation velocities of the pelvis and thorax were determined and separation time, defined as the time between the maximal rotation velocities of the pelvis and thorax, was calculated. Peak thorax rotation velocity was not associated with throwing velocity. However, separation time appeared to be significantly and positively associated with throwing velocity. Also, the changes in separation time from T1 to T2 were significantly and positively associated with the observed increase in throwing velocity from T1 to T2. There was no significant association between the changes in pelvis or thorax peak rotation velocities from T1 to T2 and the change in throwing velocity. Results indicate that the relative timing of pelvis and thorax peak rotation velocity in pitching fastballs in baseball is likely to be a determinant of throwing velocity in skilled pitchers.